Comparison of the effects of remifentanil and remifentanil plus lidocaine on intubation conditions in intellectually disabled patients - Eyigor,Can (2014)
BACKGROUND AND OBJECTIVES: This is a prospective, randomized, single-blind study. We aimed to compare the tracheal intubation conditions and hemodynamic responses either remifentanil or a combination of remifentanil and lidocaine with sevoflurane induction in the absence of neuromuscular blocking agents. METHODS: Fifty intellectually disabled, American Society of Anesthesiologists I-II patients who underwent tooth extraction under outpatient general anesthesia were included in this study. Patients were randomized to receive either 2 μg kg-1 remifentanil (Group 1, n = 25) or a combination of 2 μg kg-1 remifentanil and 1 mg kg-1 lidocaine (Group 2, n = 25). To evaluate intubation conditions, Helbo-Hansen scoring system was used. In patients who scored 2 points or less in all scorings, intubation conditions were considered acceptable, however if any of the scores was greater than 2, intubation conditions were regarded unacceptable. Mean arterial pressure, heart rate and peripheral oxygen saturation (SpO2) were recorded at baseline, after opioid administration, before intubation, and at 1, 3, and 5 min after intubation. RESULTS: Acceptable intubation parameters were achieved in 24 patients in Group 1 (96%) and in 23 patients in Group 2 (92%). In intra-group comparisons, the heart rate and mean arterial pressure values at all-time points in both groups showed a significant decrease compared to baseline values (p = 0.000) CONCLUSION: By the addition of 2 μg/kg remifentanil during sevoflurane induction, successful tracheal intubation can be accomplished without using muscle relaxants in intellectually disabled patients who undergo outpatient dental extraction. Also worth noting, the addition of 1 mg/kg lidocaine to 2 μg/kg remifentanil does not provide any additional improvement in the intubation parameters.